翻译功能与译语文化 ：以目的论来探析新加坡式英语译版的《小王子》= Translation function and target language : a study on Singlish translation “The Leeter Tunku” from the perspective of skopos theory - 林嘉欣 Lim, Jia Xin (Nanyang Technological University, 2020)
原作《小王子》于1943年出版在市面上，以诗意的童话形式讲述了一段真挚感人的故事。这本“童话”只有27个章节，虽然篇幅短但却充满了寓言和哲学道理，所以读者能回味许久以及丰富联想。因此，小说收获了众多的喜爱和争议，甚至创造了出版、翻译和销售的记录。迄今市面上，已出现300多种译本。其中就包括魏俐瑞于2019年出版的新加坡式英语译版的 The Leeter Tunku。 魏俐瑞的译作获得了不少读者的青睐，销售成绩也相当亮眼。这很有可能是因为译入语本身所处的语境下而造就的现象。新加坡式英语深受国人的喜爱，却长期受到官方和权力的压制，所以尚未从”口语化“语言转至”书面语“上。而The Leeter Tunku是第一本新加坡式英语译版的经典文学作品，并且是少数全篇使用新加坡式英语的书写文本。 然而，如果以传统翻译理论为准来评析这部译作的话，它是不合格的。因为译入语性质的关系，译作在许多方面并没有忠实于原作。但若从翻译目的论的视角下来评价此译本，它或许是个合格的翻译。再者，新加坡式英语的翻译是一个相当新的课题，所以本文将以魏俐瑞的译文The Leeter Tunku为重点研究对象。希望能够通翻译目的论来分析和探讨其翻译的策略和方法，以及译者如何通过归化和创造性叛逆来推广新加坡式英语和反抗社会语言地位权力。 Antoine de Saint-Exupéry’s The Little Prince was published in 1943. The novella comprises 27 chapters and speaks of fables and philosophical principles poetically, leaving readers with much room for imagination and interpretations. This novella has gained so much popularity and controversy that it has seen a record high in its publication, translation and sales. So far, more than 300 different translations have been published. Amongst them is a Singlish version, The Leeter Tunku, that was published in 2019 and translated by Gwee Li Sui. Gwee Li Sui’s translated version of The Little Prince has won the hearts of many readers, achieving an impressive sales record since its publication. This could be seen as a phenomenon that is created in the context of its target language. Singlish has always been part of the Singaporean identity, that is well-loved by many. However, due to restrictions and control, Singlish has not been made an official language of Singapore. Hence, even till today, Singlish has not been able to switch from being a spoken language to a written language. The Leeter Tunku is the first classic literary work translated to Singlish and published as a book. Despite being one of the few written texts in Singlish, it may have been unfair to employ traditional translation theories in evaluating this translated text. This could be attributed to the nature of its target language, Singlish, which might result in failing to achieve the closest natural equivalence in meaning to its source language. However, if Skopos Theory was utilised to evaluate this translated work, it may be appropriately accepted as a fair analysis. Furthermore, Singlish Translation is a fairly new topic of analysis. Therefore, this paper aims to study Gwee Li Sui's translation work, The Leeter Tunku, using Skopos Theory to analyse and discuss the various translation strategies and methods employed. It will also address Singlish and its language status in Singapore, as well as how translator Gwee Li Sui promotes Singlish through the use of domestication and creative treason in his translated work.